Enhanced mucosal re-epithelialization induced by short chain fatty acids in experimental colitis - Aguilar-Nascimento,J.E. (1999)
The short chain fatty acids (SCFA) are the best nutrients for the colonocytes. Glucose is poorly used as a fuel but may be transformed into SCFA by colonic bacteria. The aim of this study was to investigate the effect of SCFA or glucose on experimental colitis. Colitis was induced in 30 Wistar rats by colonic instillation of 4% acetic acid. Five days later they were randomized to receive twice a day colonic lavage containing saline (controls, N = 10), 10% hypertonic glucose (N = 10) or SCFA (N = 10) until day 8 when they were killed. At autopsy, the colon was removed and weighed and the mucosa was evaluated macro- and microscopically and stripped out for DNA assay. Data are reported as mean ± SD or median [range] as appropriate. All animals lost weight but there was no difference between groups. Colon weight was significantly lower in the SCFA group (3.8 ± 0.5 g) than in the control (5.3 ± 2.1 g) and glucose (5.2 ± 1.3 g) groups (P<0.05). Macroscopically, the severity of inflammation was less in SCFA (grade 2 [1-5]) than in control (grade 9 [4-10]) and glucose-treated (grade 9 [2-10]) animals (P<0.01). Microscopically, ulceration of the mucosa was more severe in the glucose and control groups than in the SCFA group. The DNA content of the mucosa of SCFA-treated animals (8.2 [5.0-20.2] mg/g of tissue) was higher than in glucose-treated (5.1 [4.2-8.5] mg/g of tissue; P<0.01) and control (6.2 [4.5-8.9] mg/g of tissue; P<0.05) animals. We conclude that SCFA may enhance mucosal re-epithelialization in experimental colitis, whereas hypertonic glucose is of no benefit.